The study of low-load stress measurement algorithm - Shimada, Takamasa; Sayama, Yukikazu; Sakata, Osamu (Transactions of Japanese Society for Medical and Biological Engineering, 2021)
We investigated a low-load stress measurement algorithm using tablets and verified its effectiveness. The subjects took the Kleperin test as a stressor, and before and after that, they were ordered to move their finger to unlock the pattern lock on the tablet screen. At the same time, their heart rates were measured. From the measurement results, a strong negative correlation was found between the speed of finger movement and the heart rate after taking the Kleperin test. This indicates that the speed of finger movement may reflect the activity of the sympathetic nerve. Next, we investigate the relative error (stability) of the finger. As a result, after taking the Kleperin test, the stability decreased in the stroke of moving right to left. This indicates that there may be a negative correlation between stability and stress. In the future, we plan to study more effective measurement and evaluation methods.